Monocyte chemoattractant protein 1 and macrophage cyclooxygenase 2 expression in colonic adenoma. Issue 1 (5th August 2005) - Tanaka, S; Tatsuguchi, A; Futagami, S; Gudis, K; Wada, K; Seo, T; Mitsui, K; Yonezawa, M; Nagata, K; Fujimori, S; Tsukui, T; Kishida, T; et al.
Abstract : Background and aims: Cyclooxygenase 2 (COX-2) expression in subepithelial macrophages of colorectal adenoma has been suggested as the first in a series of steps leading to colorectal tumorigenesis. We tested the hypothesis that chemokines released from human colorectal adenoma epithelium might be involved in COX-2 expression in macrophages of the lamina propria. Methods: Endoscopic samples of sporadic colorectal adenomas were tested by enzyme linked immunosorbent assay for chemokines involved in macrophage chemotaxis. Localisation of adenoma macrophage chemoattractant protein 1 (MCP-1) and COX-2 were determined by immunohistochemistry. The effects of MCP-1, in the presence or absence of celecoxib, on COX-2 expression, and prostaglandin (PG) E2 and vascular endothelial growth factor (VEGF) release, were examined in human macrophages isolated from peripheral blood. Results: MCP-1 levels were markedly higher in adenoma with mild-moderate dysplasia (129.7 (19.9) pg/mg protein) and severe dysplasia (227.9 (35.4) pg/mg protein) than in normal colonic mucosa (55.8 (4.2) pg/mg protein). Other chemokine levels, macrophage inflammatory proteins (MIP)-1α and MIP-1β, and the chemokine regulated on activation of normal T cell expressed and secreted (RANTES) did not vary significantly between adenoma and normal mucosa. MCP-1 levels in both adenoma and normal colonic mucosa increased significantly three hours after tissue cultivation in vitro. MCP-1 immunoreactivity was restricted to the adenoma epithelium, with no reactivity seen in adjacent normal epithelial cells. MCP-1 stimulated COX-2 expression and PGE2 and VEGF release in human macrophages. Celecoxib, a selective COX-2 inhibitor, inhibited MCP-1-induced PGE2 and VEGF release in macrophages. Addition of exogenous PGE2 reversed this inhibitory effect on VEGF release, suggesting that MCP-1 in adenoma epithelial cells might be involved in COX-2 expression and subsequent macrophage activation. Conclusions: MCP-1 in colorectal adenoma epithelial cells might be involved in macrophage migration and COX-2 expression, leading to the subsequent development of colonic adenoma.